Pengolahan Air Sungai Musi Menggunakan Nanopartikel Perak dari Eceng Gondok (Eichhornia Crassipes) dengan Alat Filtrasi Sederhana - Yudesta, Prayoga (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Water pollution is a significant global environmental challenge caused by domestic, industrial, and agricultural waste containing hazardous pollutants such as heavy metals and pathogenic microorganisms. Conventional water treatment methods often have limitations and produce hazardous byproducts. Therefore, this study proposes an innovative approach using silver nanoparticles (AgNPs) synthesized in an environmentally friendly manner from water hyacinth (Eichhornia crassipes) as a more environmentally friendly and sustainable alternative. The best AgNPs were found at a ratio of 2:8 with an incubation time of 120 hours, producing a wavelength of 439 nm, which indicates the optimal particle size for water treatment. The application of these optimal AgNPs in Musi River water treatment was evaluated based on BOD, COD, TSS, pH, and TDS parameters with varying operating times (10, 15, 20, 25, and 30 minutes). The results showed that a contact time of 30 minutes provided optimal water treatment efficiency, meeting the drinking water quality standards in accordance with Government Regulation No. 22 of 2021. The BOD value decreased to 1.9 mg/L (from 6.3 mg/L), COD to 8 mg/L (from 35 mg/L), TSS to 37 mg/L (from 78 mg/L), pH stabilized at 7.1 (from 6.3), and TDS to 561 mg/L (from 1230 mg/L).